2017
DOI: 10.1534/genetics.116.191957
|View full text |Cite
|
Sign up to set email alerts
|

The Caenorhabditis elegans NF2/Merlin Molecule NFM-1 Nonautonomously Regulates Neuroblast Migration and Interacts Genetically with the Guidance Cue SLT-1/Slit

Abstract: During nervous system development, neurons and their progenitors migrate to their final destinations. In Caenorhabditis elegans, the bilateral Q neuroblasts and their descendants migrate long distances in opposite directions, despite being born in the same posterior region. QR on the right migrates anteriorly and generates the AQR neuron positioned near the head, and QL on the left migrates posteriorly, giving rise to the PQR neuron positioned near the tail. In a screen for genes required for AQR and PQR migra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 58 publications
0
16
0
Order By: Relevance
“…A recent report showed NFM-1, possibly in muscles, genetically interacts with SLT-1/Slit to guide Q neuroblast migration. Intriguingly, a fosmid-derived wild-type copy of NFM-1 could fully restore viability of the nfm-1 mutant (Josephson et al 2017). This inconsistency may occur because fosmid-derived constructs tend to be more resistant to germline suppression than a transgene array (Sarov et al 2012) The core kinase of the Hippo pathway is the MST/Hpo kinase, which receives signals from upstream and phosphorylates and activates LATS/warts kinase.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent report showed NFM-1, possibly in muscles, genetically interacts with SLT-1/Slit to guide Q neuroblast migration. Intriguingly, a fosmid-derived wild-type copy of NFM-1 could fully restore viability of the nfm-1 mutant (Josephson et al 2017). This inconsistency may occur because fosmid-derived constructs tend to be more resistant to germline suppression than a transgene array (Sarov et al 2012) The core kinase of the Hippo pathway is the MST/Hpo kinase, which receives signals from upstream and phosphorylates and activates LATS/warts kinase.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study shows that Merlin and Kibra colocalize at the apical membrane of epithelial cells and recruit Hpo kinase to the apical membrane for activation in parallel to Extended (Su et al 2017). C. elegans has one homolog of NF2/Merlin, NFM-1 (Göbel et al 2004;Josephson et al 2017). NFM-1 shares some characteristics of the Merlin/NF2, including the FERM domain at the N-terminus following the a helix domain (Figure 4A).…”
Section: Wts-1 Regulates Subcellular Localization Of Yap-1 In the Intmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the Q descendants, PQR migrates furthest to the posterior behind the anus, and AQR migrates furthest anteriorly to a position near the posterior pharyngeal bulb ( Figure 1C,D) (Sulston and Horvitz 1977;White et al 1986;Chapman et al 2008). The position of AQR and PQR has been a sensitive method to identify new mutations that perturb Q migrations (Chapman et al 2008;Sundararajan et al 2014;Sundararajan et al 2015;Josephson et al 2017).…”
Section: Mutations In Etr-1/celf Perturb Directional Aqr and Pqr Migrmentioning
confidence: 99%
“…The neurofibromatosis type 2 (NF2) protein Merlin is a tumor suppressor protein known to be expressed in supportive tissue of the peripheral nervous system and in a variety of other organs of the body [ 1 ]. More recently, it was shown that Merlin is also expressed in the central nervous system, in particular in neurons, neural precursor cells and astrocytes [ 2 6 ]. Inactivation of the Nf2 gene in the germ line leads to the development of benign schwannomas, meningiomas and gliomas, tumors that endanger the patient by compressing important structures of the nervous system [ 7 – 10 ].…”
Section: Introductionmentioning
confidence: 99%